The face of Non‐photosensitive trichothiodystrophy phenotypic spectrum: A subsequent study on paediatric population - Giulia Pascolini; Martina Lipari; Federica Gaudioso; Luca Fania; Giovanni Di Zenzo; Biagio Didona (Molecular Genetics & Genomic Medicine, 2024)
Abstract Background Non‐photosensitive trichothiodystrophies (TTDs) are a diverse group of genodermatoses within the subset of conditions known as “sulphur‐deficient brittle hair” syndromes. A part of them has only recently been identified, revealing novel causative genes and very rare phenotypes of these genetic skin disorders. At the same time, the molecular basis of previously published and unresolved cases has been revealed through the introduction of innovative genetic techniques. We have previously described the facial phenotype of patients with the Photosensitive form of TTD during childhood. This study marks the beginning of an effort to expand the analysis to include individuals of the same age who do not have photosensitivity. Methods A total of 26 facial portraits of TTD paediatric patients with Non‐photosensitivity from the literature were analysed using computer‐aided technologies, and their facial features were examined through a detailed clinical review. Results Distinct facial features were identified in both Photosensitive and Non‐photosensitive TTDs. Conclusion The present study has comprehensively elucidated the facial features in TTDs, encompassing the Non‐photosensitive clinical spectrum.